Simple mathematical model of field efficiency and quantification of its components for animal drawn wheeled tool carrier - Lal, Harbans (Pesquisa Agropecuaria Brasileira, 2014)
Operational field efficiency in agricultural operations estimates the amount of area not worked due to time consumed in machine preparation, transport of the machine from farmstead to the field and back, inappropriate utilization of the working width, turning time at each end and other interruption during the working day. The operational efficiency in terms of various time components can be expressed in a mathematical model: Ro = [To/(Te + Th + Ta)] x 100. Based on this model, a simpler model has been elaborated for field efficiency relating it to parameters such as speed of operation (V), turning time (T) and time efficiency (Eft), which can be easily measured in the field through sampling. The paper tests this simple model with variation of different independent variables based on literature, and figures obtained during field experimentation, to evaluate the effects of length of run, number of attachment, type of operation and wheeled tool carrier which could affect V, T and Eft.